An alternating treatment comparison of oral and total communications training programs with echolalic autistic children. - Barrera, R D (1983)
An alternating treatment comparison was conducted of the relative effectiveness of oral and total communication training models for teaching expressive labeling skills to three echolalic autistic children. The results of this comparison demonstrated that total communication proved to be the most successful approach with each of the subjects. In addition, the replication of these findings both within and across subjects suggest that total communication may be, in general, the most effective of these two training models for teaching basic vocal language skills to echolalic children. A number of hypotheses are presented that may provide a basis for the demonstrated effect.